Prevalence of Phonological Articulation Disorders in Preschool Children in the City of Skopje - Grigorova, Evgenija; Gordana Ristovska; Jordanova, Nada Pop (Macedonian Academy of Sciences and Arts/SCIENDO, 2020)
Speech communication is a complex process based on the function of the central nervous system, and also on the speech mechanisms conditioned and controlled by auditory perception, verbal memory, intellectual activity and peripheral speech apparatus.The aim of this study was to determine the prevalence of the most common phonological articulation disorders in preschool children, from 4-6 years old.
Keywords: speech disorders; preschool children; cross-sectional study; global articulation test; triple test